Expanding the possibilities of treatment and prevention of venous thromboembolic complications in cancer patients. The role of oral anticoagulants - R. A. Bredikhin; R. V. Akhmetzyanov; R. N. Khayrullin (Klinicist)
Improving the quality of care for patients with oncological diseases due to the improvement of methods of chemoradiotherapy and surgical interventions, accessibility and modernization of diagnostic potential, is accompanied by a steady increase in the frequency of venous thromboembolic complications, which occupy one of the leading places among the causes of death.Patients with oncological diseases are subject to various risk factors for thromboembolic complications, which are caused by the presence of a malignant neoplasm, due to the development of many coagulation abnormalities, initiating not only an increased tendency to thrombosis, but also a tendency to bleeding. Cancer-associated venous thrombosis, growing out of the framework of certain medical specialties, act as comorbid pathological conditions that require an interdisciplinary approach in developing rational methods of prevention and treatment. Improving the understanding of the pathophysiological mechanisms of venous thrombosis in cancer patients contributes to the development of modern methods of prevention and treatment, among which anticoagulant therapy plays a dominant role. The appearance of oral anticoagulants on the pharmaceutical market, the effectiveness and safety of which is confirmed by a series of randomized clinical trials, opens up new prospects for improving the quality of life and long-term survival in patients with malignant neoplasms.